Analisis tata kelola keuangan pada gereja kristen indonesia merisi indah - Gabriela Mony, Trice Febrinda; Suhartini, Dwi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Good Corporate Governance need to be applied to all organizations, including non-profit organizations, especially in religious non-profit organizations (Church). The principles of Good Corporate Governance consist of transparency, accountability, responsibility, independence, and fairness and equality. This study aims to analyze the implementation of Good Corporate Governance through the principles of Good Corporate Governance in Gereja Kristen Indonesia (GKI) Merisi Indah. The data analysis technique that used in this research is descriptive analysis. The conclusion of this research explained that transparency, responsibility, independence, and fairness and equality principles at GKI Merisi Indah have been implemented very well, but the principle of accountability in its implementation is quite good but there are still things that need to be improved. The results of this research can be used as a source of reference and further researches in determining whether Good Corporate Governance in other non-profit organizations has been implemented properly or not. Therefore, it is recommended to implement the principles of Good Corporate Governance because the implementation of the principles of Good Corporate Governance can make the Church a good and healthy non-profit organization.